Na gruzach imperium. Ukraina po upadku cesarstwa rosyjskiego: od rewolucji lutowej 1917 do traktatu brzeskiego 1918 - Hołubko, Wiktor; Lityński, Adam (Czasopismo Prawno-Historyczne, 2018)
Revolution of 1917 in the Russian Empire took place in February (according to the Julian calendar) or in March (according to the Georgian calendar used in Western Europe). As a result, Tsar Nicholas II of Russia abdicated in the first phase of the revolution which caused the fall of the Romanov dynasty. Consequently, the Provisional Government was brought into power. At the time, the First World War was ongoing and Russia suffered severe defeats in the conflict. The country was ruled by chaos and various political groups were fighting against each other. Furthermore, many nations started their fight for independence from the Russian Empire. The most significant events took place in Ukraine. The national activists set up their own governmental authority – Central Council of Ukraine. And, at the same time, various domestic conflicts took place in Ukraine as well. The situation was very complicated then as a 600 kilometer-long front line ran across Ukraine. Moreover, most of the country was occupied by German and Austria-Hungarian armies. It is common knowledge that the Bolsheviks led their forces against the Provisional Government in Petrograd, which was the contemporary capital of Russia (modern-day Saint Petersburg), in October / November 1917. The Bolsheviks seized power in Russia and, in consequence, the Russian Civil War started. The Bolsheviks were in no position to continue fighting in World War I and so they signed a separate peace treaty with Germany and Austria-Hungary in March 1918 in order to focus on the Russian Civil War. Ukraine, which was independent at the time, also signed a separate peace treaty with Germany and Austria-Hungary. A new phase in the war between Russia and Ukraine started which Ukraine eventually lost.